Implementasi Algoritme Grain V1 Dan 128 Bit Pada Arduino Mega 2560 - Ajeng Nurrohmah; Ari Kusyanti; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Technology developments demanded cutting-edge data security systems, especially on hardware systems. NIST (National Institute of Standard Technology) is an institution that oversees data security standards. NIST organized an eSTREAM project to search for new stream cipher algorithms for various hardware and software application profiles. The algorithm chosen for hardware is the grain algorithm. Grain algorithm is superior because the architecture has a complex level of complexity so that the level of security is higher. The algorithm has two versions v1 and 128 bit. This research tells how to use grain algorithm to secure data on hardware side applied to arduino mega. Researchers chose arduino mega due to the use of this microcontroller in the IoT and there is no update data security using the latest stream cipher. Conducted 3 stages of testing that is validation test vector, performance analysis between grains through the execution time keystream and data encryption and decryption. This research yielded keystream validation in accordance with test vector. The results were analyzed using Independent t-test statistic test, with the result of Sig's keystream execution time. 0.662 then there is no significant difference in the performance of grain algorithm v1 and 128. While the results of the execution time of encryption and decryption of both algorithms also have no significant differences, indicating that arduino mega has a stable performance in running both algorithms.